Comparison of the Quality of Maternal and Child Health Services between City Health Centers and Rural Health Centers in Banyuwangi Regency, East Java - Nazwha (Generasi Sains Indonesia, 2024)
This study examines the excellent of maternal and infant health offerings in Banyuwangi Regency, East Java, evaluating town fitness centers (Puskesmas Kota) with rural health centers (Puskesmas Pedesaan). Using a pass-sectional layout and stratified random sampling, records were collected from individuals regarding demographics, service utilization, and pride ranges. Descriptive records, paired-samples t-checks, regression analysis, ANCOVA, and Pearson correlation had been employed for records evaluation. The consequences found out variations in player traits and service utilization patterns between city and rural settings. However, both kinds of fitness facilities showed large enhancements in participant pleasure publish-carrier. Regression evaluation diagnosed age, training, profits, and provider usage as predictors of pleasure levels. ANCOVA highlighted the significance of provider utilization in influencing pleasure, at the same time as Pearson correlation analysis underscored the interconnectedness of demographic elements and service usage with pleasure stages.